Revealing Fraudulent Practices in Management of Community Group Regional Grant Funding - Faisol, Faisol; Haryadi, Bambang; Musyarofah, Siti (Association of Certified Fraud Examiners Indonesia Chapter, 2024)
Grant funds are a Provincial Government program that is disbursed to recipients of grant funds, namely community groups, to improve community welfare through infrastructure development such as road asphalting, concrete rebates, retaining walls, and other programs. This research aims to describe fraudulent practices in managing regional grant funds for community groups starting from planning, implementation, and accountability. This research uses descriptive qualitative methods by collecting data through interviews, observation, and documentation. The results of this research found that the fraudulent practice of managing regional grant funds for community groups began when the proposal was ratified, where there was an act of gratification aimed at speeding up the ratification of the grant fund proposal. During the disbursement of grant funds, unreasonable deductions were practiced by community group coordinators. This practice was carried out for the management of community groups starting from submitting proposals to preparing accountability reports. Fictional physical development activities have a strong backing, the aim is to embezzle and profit from the grant budget. Furthermore, grant fund fraud actors colluded with related agencies so that physical construction that did not comply with budget plans escaped supervision.